Shear strength comparison of single lap and joggle lap adhesive joints in carbon fiber composites manufactured via vacuum-assisted resin infusion - Pratama, Mikhael Gilang Pribadi Putra; Abdurohman, Kosim; Pratomo, Rezky Agung; Hidayat, Ryan; Ramadhan, Redha Akbar; Aritonang, Rian Suari; Nurtiasto, Taufiq Satrio; Ardiansyah, Riki; Nugroho, Afid; Nuranto, Awang Rahmadi; Wandono, Fajar Ari; Targani, Dudi; Ula, Nur Mufidatul (Politeknik Negeri Lhokseumawe, 2024)
The extensive utilization of composite materials has spurred the advancement of diverse joining techniques suitable for components constructed from such materials. This study focuses on the examination of two specific types of joints: single lap and joggle lap joints. The specimens utilized were composed of unidirectional carbon fiber composite combined with vinyl ester resin, manufactured via the vacuum-assisted resin infusion method. Vinyl ester adhesives were employed in the bonding process, with the joint surfaces undergoing sanding treatment prior to testing. Mechanical testing was conducted on the specimens according to ASTM D5868 standard, employing a constant crosshead speed until failure occurred. The test results reveal that the shear strength of single lap joints surpasses that of joggle lap joints. Within the single lap joint configuration, a mixed failure mode comprising both adhesive and cohesive failure is observed. Conversely, in joggle lap joints, substrate delamination is prevalent, suggesting the predominance of peel stress during loading.